Bilateral central and centrocaecal scotomata due to mass lesions. Issue 5 (May 1984) - Gutman, I; Behrens, M; Odel, J
Abstract : Unilateral central or centrocaecal scotoma may result from optic nerve compression. However, such defects bilaterally usually indicate non-compressive optic neuropathy of toxic or nutritional, hereditary, or demyelinating origin. Three cases are reported of patients who presented with somewhat atypical bilateral central or centrocaecal scotomata and were found to have suprasellar mass lesions demonstrated by CT scan and confirmed neurosurgically.